Devising a method for increasing data transmission speed in monitoring systems based on the mobile high-density internet of things - Kuchuk, Heorhii; Mozhaiev, Oleksandr; Tiulieniev, Serhii; Mozhaiev, Mykhailo; Kuchuk, Nina; Tymoshchyk, Liliia; Lubentsov, Andrii; Onishchenko, Yurii; Gnusov, Yurii; Tsuranov, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process that improves the efficiency of data transmission in monitoring systems that arrive from low-power devices within the mobile high-density Internet of Things. The task addressed was to reduce the average delay time of information transmission through the transmitting station of the monitoring system gateway. To this end, it was proposed to improve the multiple output procedure and use the technique for building temporary dynamic clusters of dependent sources. During the research, a model of a monitoring system with multiple node outputs was built. Its process involved the procedure for constructing a temporary subset of active devices dependent on data. That made it possible to reduce the redundancy of data coming to the monitoring system gateway. An approach has been proposed for finding the values of the upper and lower limits of the average data transmission delay. The approach is based on simplifying calculations by switching to a one-dimensional Markov chain. The use of a uniform distribution of active subscribers has made it possible to find an analytical expression for the upper limit of the average delay. A feature of the lower bound calculation process is the introduction of a fixed division of the receiving zone of the transmitting station into equal sectors. The algorithm developed for multiple node output is aimed at reducing the average data transmission delay with a limited number of subscribers. A feature of the method is the limitation of the number of transitions when forming a stationary distribution of the Markov chain. As a result of using the method, the average delay is reduced and the speed of data transmission increases. Studies of the proposed method have shown that the speed of data transmission increases in comparison with existing methods from 5 to 50%. The research results are attributed to the use of the procedure of multiple subscriber output